Hubungan Partus Lama dan Berat Badan Lahir Bayi dengan Robekan Perineum Pada Ibu Bersalin di Puskesmas Wara Kota Palopo - Fitri H. Sudiamin; Fadliyah Fadliyah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
A perineal tear is a tear that occurs at the time the baby is born either spontaneously or with a tool or action. The impact of perineal tears can result in continuous bleeding and infection of suture wounds in the birth canal, slow treatment can cause death in postpartum mothers to find out the relationship between the old partus and the baby's birth weight with perineal tears in pregnant women at the Wara Health Center, Palopo City in 2021. This study is a quantitative analytical research with a